2020
DOI: 10.1016/j.apnr.2020.151340
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Roy Adaptation Theory to a care program for nurses

Abstract: Theory-guided nursing practice is foundational in providing the framework for the development of excellent nursing care. There is a need for effective care programs for nurses, whereby they are adequately supported within their workplace infrastructures as a professional group whose work is essential to the provision of healthcare worldwide. Likewise, there is a need for care programs for nurses to be theory-guided. In the current global pandemic climate, the well-being of nurses continues to become compromise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Characteristics of the profession also included the usefulness of nursing and the existence of a specialized body of knowledge 59 . Some studies also analyzed a number of nursing theories and concluded that nursing theories can be used not only to guide nurses' practice—even in the COVID‐19 pandemic—but also can serve as a guide in the development and evaluation of a hospital‐based programs to support nurses and improve their group identity 60,61 . Therefore, nursing theories as specific nursing knowledge can, directly and indirectly, improve both the quality of care and nurses' and nursing students' self‐evaluation and interest in the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the profession also included the usefulness of nursing and the existence of a specialized body of knowledge 59 . Some studies also analyzed a number of nursing theories and concluded that nursing theories can be used not only to guide nurses' practice—even in the COVID‐19 pandemic—but also can serve as a guide in the development and evaluation of a hospital‐based programs to support nurses and improve their group identity 60,61 . Therefore, nursing theories as specific nursing knowledge can, directly and indirectly, improve both the quality of care and nurses' and nursing students' self‐evaluation and interest in the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Roy's theory states that physical stimulus is one of the external factors of a regulator coping mechanism [18]. It is expected that with coping mechanisms, someone can achieve four adaptive modes that aim to improve their adaptation to contribute to the health and quality of life and to provide adaptive responses [19], [20].…”
Section: Relationship Physical Activity and Anxiety With Pms In Adole...mentioning
confidence: 99%
“…Type 2 diabetes mellitus (DM) is a global chronic disease that has been increasing in prevalence every decade, with 1 in 7 adults living with DM and 3 of 4 cases are from low or middle class countries [1]. Turkey is one of the counties with the highest prevalence in Europe, with about one in every seven adults diagnosed with DM.…”
Section: Introductionmentioning
confidence: 99%